Memaksimalkan Keterlibatan Pria Dalam Pelayanan Gereja Lokal Di Gpdi Majelis Wilayah I Sungai Bahar - PURBA, SUDIARJO (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The background of this study is the lack of male ministers in the local church in GPdI Sungai Bahar Region I. The research aims to look at the reasons for men's non-involvement in ministry and pinpoint areas of need for men's involvement, then encourage men to get involved in local church ministry which will have a positive impact on church ministry. The research method used a qualitative method with a descriptive approach. Data were collected through interviews, questionnaires, and observation. The scope of the research was men in local congregations in the working area of the Regional Assembly I of the Pentecostal Church in Indonesia (GPdI) Sungai Bahar, Jambi Province with a total of 88 adult men (married) from 21 local congregations. The results obtained are that many men have not been involved in the ministry because they do not fully understand the reasons and forms of involvement that they can do. The conclusion of this study is that the more men's involvement in local church ministry is maximized, the greater the achievements that can be done in the local congregation, so that serious efforts are needed from pastors to seek men's involvement in local congregations through inspirational stories from men who are involved in ministry.